Business plan: Strategic analysis of an expansion to Coimbra: Mission To Escape - Costa, Liana Gomes da (2023)
This business plan is part of the Master of Business Administration program and focuses on expanding a Lisbon-based company, Mission to Escape, to the Coimbra region. Mission to Escape is a company in the entertainment sector that has already expanded to Loures and Porto. The goal of this business plan is to study the market in which Mission to Escape operates and to design strategies that will contribute to its success in the Coimbra region. This document will also serve as a reference for decision-making and unforeseen situations that may arise during the expansion process. To create this business plan, I conducted a literature review on relevant topics, analyzed the regional market with a focus on the entertainment sector, and conducted an internal analysis of Mission to Escape as well as a competitive analysis of the market. I also characterized the sector and established the components of the marketing mix. Furthermore, as a conclusion to this dissertation, the final chapter will assess the impact of strategic control and the implementation of the Scorecard framework, with the aim of further enhancing the scope and effectiveness of this plan.